2022
DOI: 10.1097/prs.0000000000008834
|View full text |Cite
|
Sign up to set email alerts
|

Time to Stop Routinely Prescribing Opiates after Carpal Tunnel Release

Abstract: This study is registered under the name "Narcotic vs. Nonnarcotic Pain Study Protocol," ClinicalTrials.gov identification number NCT01974609 (https://clinicaltrials.gov/ ct2/show/NCT01974609).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Patients undergoing CTR at 5 centers in Canada and the United States were randomly assigned to receive opioid or OTC medication for postoperative pain control. The 347patient study found no significant differences in pain score ratings or patient satisfaction, leading the authors to opine that it is time to stop routinely prescribing opioids for CTR 41 .…”
Section: Fewer Opioids During Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Patients undergoing CTR at 5 centers in Canada and the United States were randomly assigned to receive opioid or OTC medication for postoperative pain control. The 347patient study found no significant differences in pain score ratings or patient satisfaction, leading the authors to opine that it is time to stop routinely prescribing opioids for CTR 41 .…”
Section: Fewer Opioids During Recoverymentioning
confidence: 99%
“…Emerging evidence now suggests that postoperative pain in wide-awake anesthesia patients may be managed with fewer opioids 39 or without opioids altogether [40][41][42] . Using the PearlDiver database, analysis of nearly 35,000 patients undergoing minor hand procedures showed that those managed with the WALANT technique were significantly less likely to fill an opioid prescription after CTR than patients treated with standard anesthesia 39 .…”
Section: Fewer Opioids During Recoverymentioning
confidence: 99%
“…Ibuprofen has demonstrated similar efficacy to opioids for pain relief after cosmetic, breast, hernia, skin cancer, and soft-tissue hand surgery, and has fewer side effects. [27][28][29][30] It is also more cost-effective, given its effectiveness in pain control, public tolerance, and low potential for abuse. 28 Studies in plastic and cosmetic surgery patients do not show an increased risk of bleeding with ibuprofen.…”
Section: Ibuprofen (Advil or Motrin)mentioning
confidence: 99%
“…If the patient tells me they normally take an over-the-counter, benign pain medication, I tell them: “That is all you are going to need after this operation if you follow the simple rules of keeping your hand higher than your heart and keeping it quiet until you are off all pain killers. 2 , 3 , 4 , 5 , 6 Treat it like a sleeping baby; don’t disturb it! You can take a little Advil and/or Tylenol after the freezing (numbing medicine) wears off this evening and maybe again tomorrow if you need it.…”
Section: Communication Strategiesmentioning
confidence: 99%